Therapeutic Role of Phytophenol Gallic Acid for the Cure of COVID-19 Pathogenesis - Baraskar, Kirti; Thakur, Pratibha; Shrivastava, Renu; Shrivastava, Vinoy K. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
The SARS CoV-2 virus, the causative agent of COVID-19 uses the ACE-2 receptor of the host to penetrate and infect the cell, mainly in the pulmonary, renal, and cardiac tissues. The earlier reported Delta and the recent Omicron are the variants of concern. The mutations in the RBD region of spike protein are associated with increased RBD-ACE-2 receptor interaction. This binding affinity between spike protein and the receptor is greater in Omicron than in the Delta variant. Moreover, the Omicron variant has numerous hydrophobic amino acids in the RBD region of the spike protein, which maintain its structural integrity. Gallic acid is a phytophenol and shows high binding affinity toward the ACE-2 receptors, which may be helpful for better outcomes in the treatment of COVID-19 pathogenesis. In the present study, significant data were collected from different databases i.e., PubMed, Scopus, Science Direct, and Web of Science by using keywords like anti-oxidative, anti-inflammatory, and antimicrobial properties of gallic acid, in addition to receptor-based host cell interaction of SARS CoV-2 virus. The finding shows that gallic acid can reduce inflammation by attenuating NF-ΚB and MAPK signaling pathways to suppress the release of ICAM-1, a cell surface glycoprotein; various pro-inflammatory cytokines like TNF-α, IL 1-β, IL-6, IL-10, and chemokines like CCL-2,5, CXCL-8 along with tissue infiltration by immune cells. The purpose of this review is to highlight the therapeutic potential of gallic acid in COVID-19 pathogenesis based on its strong anti-oxidative, anti-inflammatory, and anti- microbial properties.
Keywords: COVID-19